THE ABILITY OF INDIGO DANNY TO PREVENT FROM JACK TORRANCE’S MURDER IN STANLEY KUBRICK’S FILM THE SHINING - Bayu Ade Prabowo; Haryati Sulistyorini (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2016)
‘The Ability of Indigo Danny to Prevent from Jack Torrance’s Murder in Stanley Kubrick’s Film ‘The Shining’ directs him to find the signs that relate to the ability of Indigo in the film. Descriptive – qualitative method is used to find out the ability of Indigo Danny as an indigo to prevent from murder of his family in the film ‘The Shining’. Structural approach is used to find out the general description of Danny Torrance as the main character, conflicts and settings in the film, while semiotic approach is used to analyze the signs such as symbol, icon and index of Danny Torrance as the main character, which are represented by the Indigo Danny. The result shows that Danny Torrance is an unsociable, smart, indigo, curious and stubborn person. The conflicts happened are between himself, the woman in the room 237 and Jack Torrance. There were two kinds of setting used in this film, place and time that are described in this study. The signs represent Danny who has peculiar ability to prevent murder. By using his ability he knows that Jack Torrance wants to kill his family. Knowing that he prevents it by seeing the future, interacting with the ghost and telepathizing with Dick Halloran. Icons, symbols and indexes were used to prove the ability of Danny.Keywords: Indigo, Stanley Kubrick, Sign, The Shining